Megafans of the Northern Victorian Riverine Plains, SE Australia - John Webb; Karen Kapteinis; Susan White (2023)
This book provides a new inventory of nearly 300 megafans across five continents. Chapters focus on regional studies of megafans from all continents barring North America and Antarctica.